Considerações sobre o sentido do erro na escrita de crianças na perspectiva do Fonoaudiólogo e do Professor. - Brandão, Cristiane Konyi (2006)
INTRODUCTION-This work results from the necessity of reflecting about the errors committed in the field of written language of speech and hearing therapist once this area has been demanding more attention from the researchers due to the diversity of aspects that are observed in constant clinical demand. The fact is that we note an increase in the leading of patients done mainly by teachers who work with children in school age - from 7 years old on - that present difficulty in learning. It's possible to note that when the patient is leaded by the school, it's usually because of errors committed by the children in their production. We can observe in the clinical context that in many cases the teachers find difficult to deal with the appearance of errors inside the classroom and this way they decide to lead the children to a professional speech and hearing therapist like a that focus its work in the language, and particularly in this case in the written language. OBJECTIVE-The objective of this work was to investigate the sense of the errors in the written language of the children taking into account the perspective of the speech and hearing therapist and the teacher, besides looking to find possible articulations that may arise in both visions. METHOD-This way, we carried out a qualitative research where we utilized the technique of focal group with the presence of speech and hearing therapist and teachers. RESULT- The research brought as a result that the speech and hearing therapist tend to interpret the errors in a more wide and conceptual vision, such as we find in discoursive practices supported on the "letramento" concept, while the teachers still direct their look to the error as an "target", a fault reducing the writing in strictly school activities. CONCLUSION- We hope this search to make possible a new look to the errors in the speech and hearing therapist speech and hearing therapist written language of children and also to contribute to professionals like and teachers.